SQL injection prevention using hyperledger fabric - Billah, MD. Minhazul; Zahir, Adnan-Bin; Tabassum, Syeda Lamia; Siam, Tanvinur Rahman; Labib, MD. Nefaur Rahman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.